The Role of Maternal HIV Envelope-Specific Antibodies and Mother-to-Child Transmission Risk - Douglas, Ayooluwa O.; Martinez, David R.; Permar, Sallie R. (Frontiers in Immunology, 2017)
Despite the wide availability of antiretroviral therapy (ART) prophylaxis during pregnancy, >150,000 infants become infected through mother-to-child transmission (MTCT) of HIV worldwide. It is likely that additional intervention strategies, such as a maternal HIV vaccine, will be required to eliminate pediatric HIV infections. A deeper understanding of the fine specificity and function of maternal HIV envelope (Env)-specific responses that provide partial protection against MTCT will be critical to inform the design of immunologic strategies to curb the pediatric HIV epidemic. Recent studies have underlined a role of maternal HIV Env-specific neutralizing and non-neutralizing responses in reducing risk of MTCT of HIV and in prolonging survival rates in HIV-infected infants. However, critical gaps in our knowledge include (A) the specific role of maternal autologous-virus IgG-neutralizing responses in driving the selection of infant transmitted founder (T/F) viruses and (B) Env mechanisms of escape from maternal autologous virus-neutralizing antibodies (NAbs). A more refined understanding of the fine specificities of maternal autologous virus NAbs and ways that maternal circulating viruses escape from these antibodies will be crucial to inform maternal vaccination strategies that can block MTCT to help achieve an HIV-free generation.